A descriptive contrastive analysis of Thai and English personal pronoun - Vithakamontri, Raevadee 1943- (s.n.], 1969)
The study compares the personal pronoun systems of English and Thai in order to predict difficulties of Thai learners of English. Specifically, it describes the nature of the two systems based on the three aspects of form, meaning and distribution. Findings of the study show that between English and Thai are differences in the personal pronouns referring to gender, in the variations in personal pronouns used and in the different forms filling the subjective or objective slots.